PENDAMPINGAN MULTIDIMENSIONAL SCALING (MDS) UNTUK RISET PASAR DI CV AMIGO MANGESTI UTOMO - Noviana Pratiwi; Noeryanti (LPPM IST AKPRIND Yogyakarta, 2021)
Multidimensional scaling (MDS) is often associated with market research. MDS in marketresearch is used to determine the position of a store against its competitors with certaincriteria. This MDS can be used to evaluate how store services are, what consumers likeand dislike and how the store compares to its competitors. CV Amigo Mangesti Utomo isone of the retail companies in the fashion sector that continues to evaluate to improve thequality of service to its customers. For this reason, assistance is provided to conductmarket research at the Amigo group. By conducting market research assistance with MDS,the Amigo Group can find out how it stands against its competitors, know the advantagesand disadvantages of the store against its competitors and each store can make futureplans to improve services to consumers so that consumers continue to grow. Aftermentoring, each store manager knows the strengths and weaknesses of his shop amongcompetitors and understands the importance of market research, so that in the future theywill conduct market research on their customers.